PHYSICAL THERAPY DEVELOPMENT IN PAKISTAN: A ‘PARADIGM SHIFT’ - Darain, Haider (Annals of Allied Health Sciences, 2015)
Physical therapists are highly-educated health care professionals whose main roles are to maintain, restore and improve movements of individuals for the achievement of optimal independence in activities of daily living. Physical Therapists are regarded an essential part of rehabilitation and, hence, enjoy key role positions in rehabilitation sciences across the world. It is important to know that the term ‘physical therapist’ or ‘physiotherapist’ can only be used by individuals who have successfully completed either Doctor of Physical Therapy (DPT) or Bachelor of Science in Physical Therapy (BSPT) from registered institutes. Physical Therapy in Pakistan has seen drastic changes over the last two decades. Formal qualification in Physical Therapy at under graduation level was updated two times;in 1999, Physical Therapy degree, which was 3-year degree program was upgraded to 4-year degree program and then after eight years (in 2007), for the first time in the country, Doctor of Physical Therapy was introduced. With tireless efforts and dedication, Physical Therapists across the country approved curriculum of 5-year DPT program from the Higher Education Commission, Pakistan in 2011. At the moment, Pakistan is one of the few countries in the world offering DPT in Physical Therapy. The degree is accepted across the world and physical therapists from Pakistan are working in different parts of the world. The last two decade especially the last 10 years, remained a turning point for Physical Therapy profession in the country. A significant increase in the number of institutes offering Physical Therapy at the under-graduation level was observed in the country. The number of institutes offering formal education in the country has increased from 3 to 40 during the last decade. The formal degree offered in these institutes is DPT, which is recognized as a clinical/professional doctorate degree in Physical Therapy. The development observed in Physical Therapy is not limited to under-graduation courses and masters program in different discipline in Physical Therapy have been introduced by some of the institutes in the country. Moreover, PhD program in Physical Therapy were started by a couple of universities in Pakistan. Apart from allowing institutes to facilitate indigenous PhD program in Physical Therapy, the Higher Education Commission, Pakistan granted the first ever foreign scholarship for PhD program in 2010 in the country under the ‘faculty development program of Khyber Medical University, Peshawar’. The author of the editorial has successfully completed his PhD program from the United Kingdom following selection in the latter scholarship. Apart from these changes observed in the last decade, an increased number of physical therapists working in different academic institutes, tertiary care hospitals, private clinics and special institutions may be seen in the country. Other Noteworthy changes observed in Physical Therapy profession in the country included forming Physical Therapy associations and conducting research related activities by these associations and institutions. Conferences, workshops and influx of an increasing number of scientific journals in Physical Therapy are examples supporting the latter fact. This journal is also continuation of this developmental process with the aim to promote research activities amongst allied health sciences professionals in general and physical therapists in particular. Despite this ‘shift of paradigm’ in Physical Therapy in Pakistan, still, the profession is deficient in many aspects. One of the major deficiencies is lack of Physical Therapy council in the country. The process of formation Physical Therapy council was initiated few years ago. However, still the process has not been completed and no council has been formed so far. The role of Pakistan Physical Therapy Association (PPTA) in initiating the process of Physical Therapy council is admirable. With the hope that the same ‘shift of paradigm’ in Physical Therapy in the country will continue with the same momentum and sooner or later a monitoring body in the form of Physical Therapy council will be formed.